Preparation and characterization of catalytic membrane reactors - Pinos Vern̤ica; Medina Francesc; Dafinov Anton; Facultad de Ciencias Qum̕icas, Universidad de Cuenca
Los Reactores Catalt̕icos de Membrana, RCM, nos dan la posibilidad de optimizar diversos procesos industriales. La versatilidad que tienen los RCM reside en que pueden ejecutar varias funciones, como por ejemplo, filtracin̤, dosificacin̤ y catl̀isis. Este trabajo propone cuatro formas de preparacin̤ de RCM en modo contacto interfacial, para ser evaluados en remediacin̤ ambiental. Para la preparacin̤ de RCM, se emplearon membranas comerciales de fibra hueca de corindn̤. Como principal fase activa se us ̤paladio, el cual fue depositado por diferentes mťodos tales como impregnacin̤, sputtering (pulverizacin̤ catd̤ica) y microemulsin̤; tambiň se usaron nanopartc̕ulas de paladio-cobre obtenido por el mťodo del poliol. Los reactores obtenidos fueron probados en la generacin̤ in situ de perx̤ido de hidrg̤eno y la oxidacin̤ de fenol en medio acuoso a presin̤ atmosfřica y a temperatura ambiente o a 60ʻC. Los mejores resultados se obtuvieron con el RCM que contena̕ paladio por impregnacin̤. Los otros RCM presentaron en todos las pruebas una rp̀ida desactivacin̤.A membrane reactor is a device that combines a membrane separation or distribution process with a chemical reaction in a single unit. Membrane Reactors are capable of promoting a reaction process by: (1) selectively removing at least one of the products from the reaction zone through the membrane, making the equilibrium reaction shift tothe product side, and (2) supplying only a particular reactant to the reaction zone, thus giving an optimum concentration ratio of the two reactant streams. As a result, the yield can be increased (even beyond the equilibrium value for equilibrium reactions) and/or the selectivity can be improved by suppressing other undesired side reactions or the secondary reaction of products [1]. The simultaneous separation show advantages related to the process and the reaction: (1) it reduces the flow rate of the reactant stream, whilst increasing the residence time; (2) it increases thereactant concentration and hence the forward reaction rate; and, (3) it reduces product concentration, reducing the reverse reaction rate [2]. An important advantage is that in the reactor the membrane is able to retain homogeneous catalysts. Thus, it allows continuous operation without needing to separate and recycle catalysts [3]. Membrane Reactors (MR) have three generic approaches: extractors, distributors and contactors; Membrane Reactors as an extractor selectively remove certain products fromthe reaction zone [3], [4]. The MR as a distributor enhances the selectivity through optimizing of the reactant dose [3]. That is, by selectively distributing one of the reactants [5]. Both a perm-selective and a nonperm-selective membrane can be used to distribute one of the reactants [4].The Membrane Reactor as a contactor intensifies the contact between the reactants and the catalyst [3], [6], [7]. An important type of the Membrane Reactor is the Catalytic Membrane Reactor (CMR). A CMR is a device which perm selective membrane is one of the catalytic type or has a catalyst deposited in or on it [8], [9]. In the CMR, the membrane provides simultaneously the separation and reaction functions. To accomplish this purpose, it could use either an intrinsically catalytic membrane where the same material acts as a catalyst and as a membrane (e.g., zeolite or metallicmembrane), or a membrane that acts as a catalytic medium through activation, by introducing catalytic phases by either impregnation or ion exchange. In this case, a membrane only facilitates mass transfer [10], [11]. For instance, palladium membrane is used as hydrogen permselective CMR [9]. Targeted benefits of CMRs are seen at three different levels: a) process level, eliminating process units and phase changes among them. The integration of a separation function into the reactor allows reduction of the amount of process units, b) reactor level, optimizing the contact between the phases and the dosing strategy, and c) catalyst level, influencing catalysis through the chemical nature of the membrane [12].